The Dalit Reconfiguration of Modernity: Citizens and Castes in the Telugu Public Sphere - K. Satyanarayana (Duke University Press, 2016)
In Dalit Studies Ed. by Ramnarayan S; Rawat and K. Satyanarayana Eds.(2016). Durham: Duke University Press, 2016